The University Teacher: Catalyst of the Emotional-Technological-Ontological Logic in the Teaching of Exact Sciences - Derling Jose Mendoza Velazco; Elizeth Flores (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The aim of the study was to design a theoretical approach to the existing techno-ontological logical emotions of university mathematics teachers working in universities in Ecuador. The research was qualitative. For the selection of the sample, a random selection was carried out under the criterion of intentionality. Twenty (20) students and eight (8) mathematics teachers from different universities participated. For data collection, we used a participatory digital observation guide and an open-ended interview. Three categories emerged from the results: the andragogic retrotopia of being a mathematician, the emotional scar in teacher training and the educational perception of the university student. We conclude with a theoretical approach in which the deficit of professional digital training in mathematical sciences allows the emotional logic of the Ecuadorian teacher to drive him/her to portray an academic being that generates hatred and rejection in the university educational community.